5(x-1)-3(x+1)=4(x-2)

Simple and best practice solution for 5(x-1)-3(x+1)=4(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-1)-3(x+1)=4(x-2) equation:


Simplifying
5(x + -1) + -3(x + 1) = 4(x + -2)

Reorder the terms:
5(-1 + x) + -3(x + 1) = 4(x + -2)
(-1 * 5 + x * 5) + -3(x + 1) = 4(x + -2)
(-5 + 5x) + -3(x + 1) = 4(x + -2)

Reorder the terms:
-5 + 5x + -3(1 + x) = 4(x + -2)
-5 + 5x + (1 * -3 + x * -3) = 4(x + -2)
-5 + 5x + (-3 + -3x) = 4(x + -2)

Reorder the terms:
-5 + -3 + 5x + -3x = 4(x + -2)

Combine like terms: -5 + -3 = -8
-8 + 5x + -3x = 4(x + -2)

Combine like terms: 5x + -3x = 2x
-8 + 2x = 4(x + -2)

Reorder the terms:
-8 + 2x = 4(-2 + x)
-8 + 2x = (-2 * 4 + x * 4)
-8 + 2x = (-8 + 4x)

Add '8' to each side of the equation.
-8 + 8 + 2x = -8 + 8 + 4x

Combine like terms: -8 + 8 = 0
0 + 2x = -8 + 8 + 4x
2x = -8 + 8 + 4x

Combine like terms: -8 + 8 = 0
2x = 0 + 4x
2x = 4x

Solving
2x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
2x + -4x = 4x + -4x

Combine like terms: 2x + -4x = -2x
-2x = 4x + -4x

Combine like terms: 4x + -4x = 0
-2x = 0

Divide each side by '-2'.
x = 0

Simplifying
x = 0

See similar equations:

| 2+2x=-22-4x | | 5/16=x/8 | | X/8-5=-1 | | 2sin^2(0)= | | 4x+4(x-6)=32 | | 9cos(2x)=9cos^2(x)-13.5 | | 150y=4x-160 | | ln(x+5)+ln(-x+10)=ln(54) | | -2.3x-2.7=2.2+11.7 | | Tan(x)=-20 | | 3.5x-4.4x=4 | | 15x+25=95 | | 7w-3(6+2w)=3w-8 | | x^4/x^9 | | 2x+13=5x-7 | | ln(x)=2.59684 | | 9x-9=7x+29 | | X-^4/x^9 | | Mrt=2 | | 75+1.5x=25+70x | | 3m-5t=2 | | 9m+4=96 | | Rm=7 | | X^2+10x+25=625 | | 3y+65=9y+35 | | 80-what-13=10 | | 5t+2m=7 | | 4(m/2-9=-40 | | x^2+3x+x=77 | | u+3v=10 | | 3/14÷-3/7 | | 55-what-25=15 |

Equations solver categories